An analysis of the approach adopted by the South African Constitutional Court to the right to equality and non-discrimination in the five decisions concerning section 8 of the interim Constitution compared to the approach adopted by the Belgian Court of Arbitration - Boelaerts, Violaine Marie Anne (Department of Public Law, 2023)
Since time immemorial, equality is a concept which has been the subject of philosophical debate and political contest. Today, democratic society proclaims itself to be committed to the values of openness, democracy, freedom and equality. In South Africa and in Belgium, equality is a fundamental value which lies at the heart of both Constitutions. For different reasons, this right is central regarding the two Constitutional Courts. In South Africa, the importance of the decisions made by the Constitutional Court in the equality and non-discrimination field is clear given its particular history of apartheid during which deep inequalities among the population were enforced. In Belgium, equality is the key of the Court of Arbitration's competence to exercise a constitutional control regarding the fundamental rights and freedoms enshrined in the Constitution. In both jurisdictions, it is clear that equality is not simply a matter of likeness but equally a matter of difference. Because Justice and Equality do not have the same significance and must not be confused, it is important to attempt to understand and to delineate what equitable equality means in a constitutional context. This dissertation undertakes to analyse the equality jurispruden of the South African Constitutional Court by reference to its five first decisions in order to determine its current approach to section 9 of the Constitution of South Africa Act 108 of 1996 (previously section 8 of the Constitution of the Republic of South Africa Act 200 of 1993 (the interim Constitution)). After an introduction to the Belgian Court of Arbitration and review of its treatment of the right to equality and non-discrimination, its approach will be evaluated in comparative perspective.